Revisiting the question of assessment by severity and classification of acne - Elena R. Araviiskaia; Alexey V. Samtsov; Evgeny V. Sokolovskiy; Andrey L. Bakulev; Nikolay N. Murashkin; Arfenya E. Karamova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
The paper presents an analysis of different variants of acne classifications and the assessment of acne severity, carried out by the working group of the RODVK Committee for Classifications in Dermatovenereology. There is a division of acne vulgaris according to age and severity. Assessing the severity of acne is important for choosing the correct prescriptions in daily practice and for the evaluation of treatment outcomes. Most of existing acne grading systems are based either on a global grading of severity or on calculating the number of lesions in a variety of anatomic locations. For clinical practice of dermatovenereologists, as well as for educational and scientific purposes, the working group proposed to supplement the acne classification based on severity grading with counting the number of the lesions, and to take into account localization, rash prevalence and scarring when determining the acne severity.